2003
DOI: 10.1161/01.str.0000089924.43363.e3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mean Transit Time of Contrast Medium in Ruptured and Unruptured Arteriovenous Malformations

Abstract: Background and Purpose-To clarify hemodynamic risk factors for hemorrhage in arteriovenous malformations (AVMs), the mean transit time (MTT) of feeding arteries and draining veins in AVMs with and without hemorrhage was measured and analyzed. Methods-Morphological features such as the number and diameter of draining and feeding vessels and the AVM nidus volume were evaluated in 30 patients with supratentorial AVMs. The MTT of feeding arteries and draining veins was measured with the use of time-density curves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 35 publications
2
41
0
Order By: Relevance
“…The intraclass correlation coefficient (0.00 -0.20, poor; 0.21-0.40, fair; 0.41-0.60, moderate; 0.61-0.80, good; and 0.81-1.00, excellent) was used to evaluate the interobserver agreement for perfusion measurements, and perfusion ratios were compared in the 3 ROIs (2-tailed paired t test). In addition, correlation analysis was performed between the SMG and AVM hemodynamics (Spearman correlation), between the AVM nidal volume calculated by V ϭ /6 ϫ a ϫ b ϫ c (a, b, c are 3D nidal diameters measured by experienced neuroradiologists on the basis of conventional DSA) 15 and AVM hemodynamics (Pearson correlation), and between AVM flow parameters and perfusion ratios (Pearson correlation). Multiple regression analysis (stepwise) was performed to identify the potential association of AVM flow or perfusion parameters with clinical presentation and risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The intraclass correlation coefficient (0.00 -0.20, poor; 0.21-0.40, fair; 0.41-0.60, moderate; 0.61-0.80, good; and 0.81-1.00, excellent) was used to evaluate the interobserver agreement for perfusion measurements, and perfusion ratios were compared in the 3 ROIs (2-tailed paired t test). In addition, correlation analysis was performed between the SMG and AVM hemodynamics (Spearman correlation), between the AVM nidal volume calculated by V ϭ /6 ϫ a ϫ b ϫ c (a, b, c are 3D nidal diameters measured by experienced neuroradiologists on the basis of conventional DSA) 15 and AVM hemodynamics (Pearson correlation), and between AVM flow parameters and perfusion ratios (Pearson correlation). Multiple regression analysis (stepwise) was performed to identify the potential association of AVM flow or perfusion parameters with clinical presentation and risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…This is allowed by the high temporal resolution, <70 ms, of 4D-SL-MRA sequence. Moreover, as suggested in previous reports, 2,11 hemodynamic quantification could be related to the clinical presentation because a low draining-vein-to-feeder-artery TTP ratio was associated with the high rupture risk and hemorrhagic groups. This lower TTP ratio, <2.0 in all cases, may reflect higher velocities and exposure to higher vascular pressure 12 within the nidus in patients with previous hemorrhage or known angioarchitectural bleeding risk factor.…”
Section: Discussionmentioning
confidence: 52%
“…However, the results of these studies are contradictory. Some studies identified an elevated flow in feeding arteries, 35 whereas other studies found a reduced flow. 22,36 Our finding of a prolonged transit time is in accordance with disequilibrium of faster inflow, whereas outflow remains unchanged or is reduced.…”
Section: Discussionmentioning
confidence: 99%